Hello everybody!

This problem is really good

an interesting as well.

Here's what I figured out:

let (x_1;f(x_1)) and (x_2,f(x_2)) are two distinct points of the graph of f(x)

the slope between them is defined as: m = [f(x_2) - f(x_1)]/[x_2 - x_1]

but it can be also defined via the 1st derivative: m = f`(x_1) = f`(x_2)

so the system: [f(x_2) - f(x_1)]/[x_2 - x_1] = f`(x_1) = f`(x_2)

should provide us with the correct answer

However the calculations and the algebra is terrible (though I haven't got time yet to try)

so, what do you think?